DEVELOPMENT OF CRITICAL THINKING IN PHILOLOGY EDUCATION THROUGH INTERACTIVE TEACHING METHODS - Jo'rayeva Dilnoza Ro'zimat kizi (International Scientific and Current Research Conferences, 2025)
This article explores the pivotal role of interactive teaching methodologies in fostering critical thinking among students of philology. In the contemporary educational landscape, the development of analytical, evaluative, and reflective competencies has become essential for producing intellectually autonomous individuals capable of engaging with complex linguistic, literary, and cultural phenomena. The study examines various interactive pedagogical strategies, including collaborative learning, problem-based tasks, and digital engagement tools, emphasizing their capacity to cultivate higher-order thinking skills. By synthesizing theoretical perspectives with empirical evidence, the article provides insights into how structured interactivity in classroom settings enhances students’ critical cognitive processes, motivates reflective discourse, and strengthens meta-cognitive awareness in philology education. The implications underscore the necessity of integrating interactive methods into curricular frameworks to bridge the gap between traditional instruction and the demands of a rapidly evolving academic and professional environment.